PENGARUH BUDAYA ORGANISASI, TIM KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DITKERSINHAN DITJEN STRATEGI PERTAHANAN KEMENTERIAN PERTAHANAN RI - Dian Diana Rahayu; Mochammad Subagio (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2021)
Abstract :The purpose of this study was to examine the influence of Organizational Culture, Team Work and Employee Competence on the Ministry of Defence’s Employee Performance. The research was conducted at the Directorate of International Cooperation, Directorate General of Defense Strategy, Ministry of Defense of the Republic of Indonesia. The method used in this research is a causal study or path analysis. The sample of this study was 80 employees of the Directorate of International Cooperation which were taken randomly based on a Random Sampling System. From this research, it is concluded that (1) there is a direct influence of Organizational Culture on Competence, (2) there is a direct influence of the Team Work on Competence, (3) there is a direct influence of Organizational Culture on Employee’s Performance, (4) there is an influence of the Team Work on Employee’s Performance and (5) there is an influence of competence on Employee’s Performance. Based on the results of this research, we can state that a person's performance is influenced by organizational culture, teamwork, and employee competence. In this study, teamwork is a variable that has a dominant influence on the performance of the employees. So it can be said that the existence of employees in a harmonious team work will support and even improve employee performance. Finally, it can be concluded that Organizational Culture, Work Team, and Competence are considered to be able to improve the performance of the employees of Ditkersinhan, the Directorate General of Defense Strategy of the Ministry of Defence of the Republic of Indonesia.Keywords : Organizational Culture, Teamwork, Competency, Performance.